Effective venetoclax treatment for indolent T-cell lymphoma of the gastrointestinal tract: a case report and literature review - Jian, Ji-Mo; Hao, Hong-Yuan; Yuan, Cheng-Lu; Zhang, Shu-Qi; Huang, Zou-Fang; Du, Jun (Frontiers in Immunology, 2025)
Indolent T-cell lymphoma of the gastrointestinal tract (iTCL-GI) is rare, lacking standardized treatments. We report a successful venetoclax treatment in one patient with indolent T-cell lymphoma of the gastrointestinal tract. A 35-year-old male was admitted due to complaints of anemia and hematochezia. He was diagnosed with iTCL-GI according to histopathology and next-generation sequencing (NGS). He received the first cycle of CHOP-E chemotherapy, but he continued to have intermittent blood in stools. After starting oral Bcl-2 inhibitor venetoclax, the results of peripheral hemogram and the body temperature gradually turned normal, with no symptoms of hematochezia occurring again. In addition, colonoscopy showed improved ulcers in the ascending and transverse colon. Routine blood tests returned to normal without adverse effects. Therefore, venetoclax may represent a potential treatment approach for iTCL-GI. This report might provide clues for the future management of similar cases.